Supply ecosystems : Interconnected, interdependent and cooperative operations, supply and contract management - Macbeth, Douglas Kinnis (World Scientific Publishing Company, 2018)
Explores the concept of supply ecosystems, emphasizing the interconnection and interdependence of operations, supply, and contract management. Integrates perspectives from logistics, technology, and quality management to show how cooperation across supply networks creates strategic advantage in global business environments.